A Survey of Pre-Service Teachers ICT’s Competencies in Papua - Martha Betaubun (STAI Hubbulwathan Duri, 2021)
This research analyzes the ICT Competencies of Pre-services Teachers in Papua, including the Region of Sorong, Merauke, Jayapura, and Manokwari. This research aims to discover the students of Teachers' Training Faculty spread in Papua competencies on ICT. The measurement of ICT competencies is carried out using a model developed by Tondeur for preservice teachersusing questionnaires that consisted of 19 items. Questionnaires were distributed to Papua Region covering Jayapura and Merauke, West Papua region covering Sorong and Manokwari. Sixty-eight respondents became the data in this study. Data were analyzed using XL Stats to find the mean and standard deviation. The findings in this study were; the low competencies were found on Papuan Indigenous Pre-service teachers, and the high competencies were found in science discipline compared to non-science in Papua and West Papua Indonesia. The low ability of native Papuan students in managing information in the digital world is indicated by the lack of awareness of preservice teachers in developing a sense of responsibility in using ICT as a communication medium and activities involving ICT use.